2019
DOI: 10.1177/1557988319829953
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Individual: Social and Cultural Influences on the Health-Seeking Behaviors of African American Men

Abstract: Morbidity and mortality rates are alarmingly high among African American men and are influenced by the health-seeking behaviors of this population. This study examined data from 40 focus groups with African American men in Durham, North Carolina, to better understand social and cultural influences on health-seeking behaviors. Data were analyzed using inductive thematic analysis. Three broad types of social/cultural influence on motivation to seek health care services were identified: family, culture and upbrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Although we are interested in measuring the effect of women's influence on knowledge retention in the male cohort, testing that influence directly is beyond the scope of the pilot. Findings from the current study are largely in agreement and build on those of previous studies demonstrating the interest and involvement of women in the health and health care of AA communities (Allen et al, 2018(Allen et al, , 2013Eley et al, 2019;Jones et al, 2010;Plowden & Young, 2003).…”
Section: Increase In Knowledge and Awarenesssupporting
confidence: 90%
“…Although we are interested in measuring the effect of women's influence on knowledge retention in the male cohort, testing that influence directly is beyond the scope of the pilot. Findings from the current study are largely in agreement and build on those of previous studies demonstrating the interest and involvement of women in the health and health care of AA communities (Allen et al, 2018(Allen et al, , 2013Eley et al, 2019;Jones et al, 2010;Plowden & Young, 2003).…”
Section: Increase In Knowledge and Awarenesssupporting
confidence: 90%
“…Generally, the behaviour of people to engage in care and treatment is dependent on several factors including the socio-cultural environment [18, 19]. The theory of explanatory model of health and illness recognises different beliefs and notions held by people regarding disease and its treatment [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies had reported that affordability was vital in influencing the choice of treatment provider among the men who made out-of-pocket payment. [6,9,32] Also, socioeconomic factors influence the utilization of health facilities in the absence of health insurance ownership. [9,33] The majority of the respondents who did not subscribe to health insurance (HI) still depended on drug prescriptions for treatment in the last illness episode and visited chemist shops or engaged in self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of gender norm is not limited to men in Africa but extends to other parts of the globe including the United States and Europe. [32,36] Studies have shown that the description of masculinity and gender as it relates to health is very unhelpful because most men tend to visit the hospital for the curative care of advanced ailments. [30] A majority (95%) of the participants rated themselves as having generally good health and 35.8% reported very good health.…”
Section: Discussionmentioning
confidence: 99%